Look away now! Defensive processing and unrealistic optimism by level of alcohol consumption. - Morris, J.; Tattan-Birch, H.; Albery, I. P.; Heather, N.; Moss, A. C. (Psychology & Health, 2025)
Objective: Health risk information is insufficient as a means of reducing alcohol use, particularly when it evokes negative emotional states amongst those for whom it is most personally relevant. Appraisal biases, or 'defensive processing', may be employed to mitigate the psychological discomfort posed by such information. Few studies have evaluated the role of defensive processing in people with different levels of alcohol consumption. Design: Online participants (n = 597) completed measures of defensive processing of a health risk infographic, perceived susceptibility and severity of alcohol use, efficacy for resisting alcohol use, unrealistic optimism, the Alcohol Use Disorder Identification Test – Consumption (AUDIT-C) and demographics. Results: AUDIT-C scores were positively and linearly associated with all defensive processing measures (Pearson's correlation r from.16 to.36), threat and susceptibility (r =.16) and unrealistic optimism (r =.50). AUDIT-C scores were also negatively associated with efficacy for controlling alcohol use (r = −0.48). Conclusion: People with alcohol use disorder (AUD) engaged in much more defensive processing of alcohol-related messages, offering an explanation for why such messages are limited at eliciting behaviour change. High levels of unrealistic optimism in people with alcohol use disorder may reflect low problem recognition in order to maintain a problem-free drinking identity.